Optimal design of micro-dimples on crankpin bearing surface for improving engine's lubrication and friction. Issue 1 (24th July 2020) - Jiao, Renqiang; Nguyen, Vanliem; Le, Vanquynh; Bui, Vancuong
Abstract : Purpose: The purpose of this paper is to investigate the optimal design of micro-dimples on the bearing surface of the crankpin bearing (CB) to ameliorate the engine's lubrication and friction (ELF). Design/methodology/approach: A hydrodynamic model of the CB considering the influence of the asperity contact is built under the impact of the dynamic loading of the slider-crank-mechanism. The micro-dimples on non-slip surface of the bearing are designed and optimized based on the lubrication model and multi-objective genetic algorithm. The performance of optimal micro-dimples on ameliorating the ELF is analyzed and compared with that of optimal CB dimensions via the reduction of the solid contact force, friction force and friction coefficient between the crankpin and bearing surfaces; and the increase of the oil film pressure. Findings: The optimal design of micro-dimples on the bearing surface may not only greatly ameliorate the ELF but also make the rotation of the crankpin inside the bearing more stable in comparison with the optimization of CB dimensions. Originality/value: This study results not only clearly ameliorates the ELF but also can be applied to the slip/non-slip surface pairs of other journal bearings to enhance their lubrication performance.